Does neoadjuvant chemoradiotherapy for esophageal and gastro-esophageal junction cancer patients affect post-operative outcomes? A study using Becker TRG system and lymph node regression. - Maria Inês Vaz do Rosário (2022)
Background: The effect of neoadjuvant chemoradiotherapy (nCRT) in patients with locally advanced esophageal cancer can be determined by assessing tumor regression grade (TRG) in primary tumor, as well as in lymph nodes. In this study, we aim to investigate the anatomopathological changes caused by nCRT and their impact on clinical parameters. Specifically, we analyzed Becker TRG and lymph node status and regression changes and evaluated their association with the Clavien-Dindo Classification of Surgical Complications and overall patient survival. Methods: We conducted a retrospective and observational study. Our series included 139 patients diagnosed with adenocarcinoma or squamous cell carcinoma of the esophagus or esophagogastric-junction treated with either nCRT followed by surgery or surgery alone. For the 94 patients who underwent nCRT, we evaluated tumor regression by Becker TRG in primary tumors. We also analyzed lymph node status and regression changes on lymph nodes with or without metastases. Overall survival analysis was performed using Kaplan-Meier curves. Results: Becker TRG is associated with lower lymphatic permeation (p<0.01) and vascular invasion (p<0.001), but not with lymph node regression rate (p=0.10). Clavien-Dindo classification was neither associated with lymph node regression rate (OR=0.784, P=0.795) nor with TRG grade (p=0.68). Patients who presented with lymphatic permeation and vascular invasion had statistically significant lower median survival (17vs30 months; p=0.006) and (14vs29 months; p=0.024), respectively. Conclusions: In our series we were unable to demonstrate an association between Becker TRG and lymph node regression rate with any postoperative complications. Patients with lower rates of lymphatic permeation and vascular invasion have higher overall survival, correlating with a better response in Becker TRG system.